Entre a escrita e a revisão: a criação de fábulas por díades do 3º ano do ensino fundamental - Costa, Salezia Magna de Oliveira (2018)
This present work proposes at analyzing the process of textual revision, the first version of texts created by pairs of children which are students of a primary school from a public education institution in the city of Campo Alegre, state of Alagoas (Brazil). This public school has a project entitled "Read well to write better!” The current research is inserted in the field of the Textual Genetics studies (GRÉSILLON, 1994; BIASI, 2010), and is materialized through the analysis of real time writing processes (CALIL 2008, 2009), by taking into consideration collaborative writing activities, verbal interaction between pairs (DAIUTE; DALTON, 1992; JOLIBERT; 1994; CALIL; FELIPETO, 2008, 2009, 20014; BAKTHIN, 1990), and the textual revision processes (CAGLIARI, 2009, ABAURRE, SABINSON E FIAD, 1997, HAYES; FLOWER, 1980; FLOWER, HAYES; CAREY; SCHRIVER; STRATMAN, 1986; CHANQUOY, 2001, ALLAL; CHANQUOY; LARGY, 2004; SPINILLO, 2015; DOLZ, NOVERRAZ E SCHNEUWLY, 2004; CALIL, 2008; FABRE, 1986; FITZGERALD, 1987), and in the fundamentals of textuality, (ANTUNES, 2010), whether related to the planning of the text, to the composition of the textual genre or to the revision of the erasures. For the analysis of the dialogues and the manuscripts, categories included the following aspects: a) Collaboration in the planning of the text; b) The composition of the textual genre; and c) The revision events. In addition, a reflection was made on textuality concerning the dyads productions. This process involving the revision and rewriting of the second version of the text was recorded through audiovisual resources in order to investigate the whole effect of the collaborative work, which not only reveals students' concerns while writing, but also many other aspects. The cut that was made for four pairs consolidated this analysis through eight manuscripts from four writing processes were selected for the analysis. It is possible to observe in this research subjects under the effect of the literacy process, thinking about what they write and proposing textual changes, be they related to the planning of the text, the construction of the textual genre or the revision events.